Spotlight on dry aging beef: effects of loin type, aging methods, and aging time - S.L. DeGeer; C.L. Bratcher; B.A. Crozier-Dodson; D.E. Johnson; J.F. Stika; Melvin C. Hunt (Kansas Agricultural Experiment Station Research Reports, 2009)
Dry aging is an old-time process used to produce a high quality beef product marketed to high-end customers. Its most unique quality is the distinctive dry-aged flavor. Dry aging has been accomplished through many protocols over the years, but an optimum protocol has not been adopted. Practitioners of this art are very interested in providing a consistent, quality, safe product. Traditionally, dry aging is done without packaging, which places more emphasis on plant quality control practices to achieve a consistent product. This limits the number of processors that have the ability to produce dry-aged product. Packaging bags with a very high water vapor transmission rate that may simulate traditional dry aging are now available. If the quality from dry aging in these bags is equal to that obtained with the traditional unpackaged method, other processors might consider dry aging because this bag allows for less stringent facility needs and potentially greater yields. Overall, an in-thebag dry-aging system would require fewer controls and still result in decreased weight losses, which would provide a significant yield advantage. Objectives of this research were to determine the combined effects of two different dryaging methods (unpackaged and in the bag), two loin-cut styles (bone-in shell loins and boneless strip loins), and two aging times (21 and 28 days) on flavor, juiciness, tenderness, palatability, development of the unique dry-aged flavor, moisture vapor loss, and microbial growth. An additional objective was to determine effects of vacuum packaging after dry aging on dry-aged flavor stability of steaks.
Keywords: Cattlemen& #x27; s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Dry aging